A study on refurbishment of multi-family houses in Malaysia - housing developed by Kuala Lumpur City Government in the ’80s - - Murakami, Shin; Ikuta, Kyoko; Kito, Kyoko; Kawano, Norie; Mohit, Mohammad Abdul (Sydney: City Futures Research Centre, University of New South, 2010)
In Asian countries including Malaysia, a lot of new residential areas (; New towns) are developed because of the rapid population increase in urban areas during mass housing era ;60-80’s. The designs of the residential buildings provided to New Towns have been influenced by Western design based on modernism, which has different origin from Asian traditional architectures. Residents living in New Towns refurbish their dwellings in daily basis, and these refurbishments represent gaps between their diversified living requirements and the provided standards on which dwelling design is based. In this study, we carried out investigations on refurbishments by residents for multi-family houses in Kuala Lumpur. Our focus is providing the right and eligible procedures and methodologies to configure sustainable New Town houses considering Malaysian cultural aspects. We extracted three areas from large-scale residential complexes developed during early mass housing era in Kuala Lumpur as investigation targets. Questionnaires were given to the residents, 102 of whom answered them, and 37 of whom agreed photographing insides of the dwellings, sketching their living plans, and hearing their daily lives. 54 among 102 answered they had conducted some refurbishments. Major refurbishments are categorized as follows; installation/removal of walls/dividers, changes on floor/wall surface finishes, expansion to outside, addition of bay windows and window roofs. In Conclusion, ・ Relationship between residents’ ways of living and refurbishments is clarified. Residents’ living activities spread not only inside of dwellings but also to semi-external spaces such as balconies. ・ Various kinds of refurbishments including additions of window roofs and expansions to outside suggest ways how to adjust dwellings to local climate conditions and ways of living. ・ The ways of living and refurbishments show their living needs in semi-external spaces with appropriate air circulation. ・ The housing design in the future should be based on local climate, environments and cultures.